Acute Hemodynamic Effect of Acetazolamide in Patients With Pulmonary Hypertension Whilst Breathing Normoxic and Hypoxic Gas: A Randomized Cross-Over Trial - Lichtblau, Mona; Berlier, Charlotte; Saxer, Stéphanie; Carta, Arcangelo F.; Mayer, Laura; Groth, Alexandra; Bader, Patrick R.; Schneider, Simon R.; Furian, Michael; Schwarz, Esther I.; Swenson, Erik R.; Bloch, Konrad E.; et al. (Frontiers in Medicine, 2021)
Aims: To test the acute hemodynamic effect of acetazolamide in patients with pulmonary hypertension (PH) under ambient air and hypoxia. Methods: Patients with pulmonary arterial or chronic thromboembolic PH (PAH/CTEPH) undergoing right heart catheterization were included in this randomized, placebo-controlled, double-blinded, crossover trial. The main outcome, pulmonary vascular resistance (PVR), further hemodynamics, blood- and cerebral oxygenation were measured 1 h after intravenous administration of 500 mg acetazolamide or placebo-saline on ambient air (normoxia) and at the end of breathing hypoxic gas (FIO2 0.15, hypoxia) for 15 min. Results: 24 PH-patients, 71% men, mean ± SD age 59 ± 14 years, BMI 28 ± 5 kg/m2, PVR 4.7 ± 2.1 WU participated. Mean PVR after acetazolamide vs. placebo was 5.5 ± 3.0 vs. 5.3 ± 3.0 WU; mean difference (95% CI) 0.2 (−0.2–0.6, p = 0.341). Heart rate was higher after acetazolamide (79 ± 12 vs. 77 ± 11 bpm, p = 0.026), pH was lower (7.40 ± 0.02 vs. 7.42 ± 0.03, p = 0.002) but PaCO2 and PaO2 remained unchanged while cerebral tissue oxygenation increased (71 ± 6 vs. 69 ± 6%, p = 0.017). In acute hypoxia, acetazolamide decreased PVR by 0.4 WU (0.0–0.9, p = 0.046) while PaO2 and PaCO2 were not changed. No adverse effects occurred. Conclusions: In patients with PAH/CTEPH, i.v. acetazolamide did not change pulmonary hemodynamics compared to placebo after 1 hour in normoxia but it reduced PVR after subsequent acute exposure to hypoxia. Our findings in normoxia do not suggest a direct acute pulmonary vasodilator effect of acetazolamide. The reduction of PVR during hypoxia requires further corroboration. Whether acetazolamide improves PH when given over a prolonged period by stimulating ventilation, increasing oxygenation, and/or altering vascular inflammation and remodeling remains to be investigated.